Fatigue, Social Support, and Depression in Individuals With Coronary Artery Disease - Kazukauskiene, Nijole; Bunevicius, Adomas; Gecaite-Stonciene, Julija; Burkauskas, Julius (Frontiers in Psychology, 2021)
Background: Given that approximately one-third of individuals with coronary artery disease (CAD) remain severely fatigued after completion the cardiac rehabilitation, it is necessary to identify reliable intervention targets aimed at reducing fatigue. Perceived social support is closely linked to health outcomes and depressive symptoms in individuals with CAD. However, to our knowledge, the relationship between subjective fatigue levels and social support in those with CAD has not been analyzed. Objective: We aimed to examine the associations between perceived social support and subjective fatigue levels in individuals with CAD with and without depression symptoms. Methods: This cross-sectional study was comprised of 1036 participants with CAD (57±9 years, 77% men) 1-2 weeks after acute coronary syndrome. Participants completed the Hospital Anxiety and Depression scale (HADS), Multidimensional Fatigue Inventory-20, and the Multidimensional Scale of Perceived Social Support. Results: In total, 12% (n = 129) of study participants had elevated depression symptoms (HADS score ≥ 8). In individuals with CAD and depressive symptoms, after adjustment for sex, age, NYHA functional class, and anxiety, linear regression analyses showed significant inverse associations between higher social support from others and general, physical fatigue as well as reduced activity and motivation (p<.001). Following the same method of statistical analysis and control in non-depressed individuals with CAD (88%), social support from family was inversely linked to mental fatigue (p’s <.05). Similarly, social support from friends was significantly associated with lower general, physical and mental fatigue as well as reduced activity, while social support from others was significantly associated with lower general and mental fatigue (p’s <.001). The overall higher total support was linked with reduced motivation (p < .05) in the depressed study participants, while there was lower general and mental fatigue (p < .05) in non-depressed individuals. Conclusion: Fatigue and its features could be associated by the perceived social support in individuals with CAD following acute coronary syndromes. While in individuals with CAD and depressive symptoms, greater subjective fatigue is associated with less perceived social support from others, higher levels of subjective fatigue in non-depressed individuals with CAD are significantly associated with reduced perceived social support from friends.